PAI Teacher's Efforts in Applying Teaching and Learning Situations with Brainstorming Methods - Chusnul Chotimah; Samiani Samiani (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
This study was conducted to determine the extent of Pai teachers ' efforts in applying teaching and learning situations with Brainstorming methods .The research was conducted qualitatively where the source of the data comes from direct observation, the results of interviews with parties that are considered directly related to the research, the results of dukumentation and literature studies from references in line with the use of Brainstorming methods. Aside from the data sources, researchers also use questionnaires instead of interviewing students. This study uses Classroom action Research method to determine what changes to students after its application. In addition, the use of classroom Action Research is also carried out to determine the interest of students in following PAI lessons if using the same method next. This study was conducted in SMA Negeri I Ngimbang Lamongan with the subject of Class XI MIPA which amounted to 30 students but only 29 students who can attend. Based on the analysis of researchers Brainstorming method can make students better understand the material disampaiakan in addition, this method is also able to increase the interest of students as much as 7% very interested, 38% interested, 31% less interested and 24% not too interested.